(3GdEQTGO aj CUhd GdMOjKs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s; (3YKeGf Hf YHO GdQMef (B((3UdGM GdOjf(B) (3GHf YKeGf Hf ehSi Hf CHj GdfUQ GdfUQj GdTgQRhQj GdcQOj GdTQNGfj, CHh YeQh, Jbj GdOjf, GdeYQha HGHf GdUdGM,J (B643 (3g` s ((3CMeO Hf eGdc GdTGaYi s)
(3ChdgG (B:s
(3CeG HYO aEf Gddg SHMGfg deG NU gPg GdGeI RGOgG Gddg TQakG HYde GdGSfGO hgPG cJGH GNJUQ ajg eYQaI Yde GdMOjK ddTjN GHf GdUdGM bGd GdYdeGA GdMOjK KdGKI CbSGe UMjM hMSf hVYja s
(3BNQgG (B:s
(3hGJQc ebGdg ef dMGd hLgdI Yf cfjg Gh HOYg ai bdHg acai GdeMOK QaYg Gf jQJVi hjYO ef Ggd GdMOjK hMRHg BNQ GdcJGH hGdMeO ddg s
(3GNJUQ Gdfhhi GjVkG gPG GdcJGH hSeGg GdJbQjHs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B207 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B257s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B70s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs